Recidivism and Inmate Mental Illness - Bales, William D.; Nadel, Melissa; Reed, Chemika; Blomberg, Thomas G. (International Journal of Criminology and Sociology, 2017)
Purpose: With over 700,000 mentally ill inmates are held in U.S. jails and prisons, this study provides a comprehensive assessment of the effect of mental illness among released prisoners on a series of re-entry recidivism outcomes. Methods: Using a cohort of 200,889 inmates released from Florida prisons from 2004 to 2011, several recidivism outcomes are examined among 40,145 individuals with a mental health diagnosis and 10,826 with a serious mental illness are compared with inmates without a mental illness diagnosis. We control for a host of factors known to influence recidivism outcomes using binary logistic regression for one, two, and three year follow-up periods and survival analysis to assess the timing to recidivism. Results: Inmates diagnosed with any type of mental illness are significantly more likely to recidivate and among inmates with a mental illness, those diagnosed with a serious mental condition are significantly more likely to recidivate than those with a less serious mental illness diagnosis. Conclusions: Policies and practices need to ensure that in-prison and community mental health systems have sufficient resources and capacity to adequately address the needs of inmates with mental health issues to reduce the likelihood of these individuals re-offending and ultimately returning to prison.